2014
DOI: 10.1096/fasebj.28.1_supplement.916.4
|View full text |Cite
|
Sign up to set email alerts
|

Human intestinal tract length and relationship with body height (916.4)

Abstract: Despite its great importance in surgical approaches to intestinal resection, little definitive information is available on human gut tract length. Previous studies have correlated various measures with sex, age, weight, height, and “ethnic background.” Better knowledge of these relationships may aid in avoidance of surgical complications such as the nutritional disorder “short bowel syndrome.” This study examined length of the intestinal tract and its components (small intestine and colon) in 10 donor bodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Furthermore, BMI’s negative association with gut microbiome alpha diversity, and positive association with intestinal inflammation (which can cause shortening of the bowel through smooth muscle contractions), pushes against the overall positive scaling we see between body mass and diversity across vertebrates [ 75 , 79 ]. Thus, we used height, which has been shown to be positively associated with bowel length [ 83–86 ], as an obesity/inflammation-independent proxy for measuring body size in humans. Overall, we were able to control for all of these potentially confounding variables in our regressions, and we found that the associations between height and gut alpha diversity were robust to the inclusion of these variables across two large, independent cohorts ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, BMI’s negative association with gut microbiome alpha diversity, and positive association with intestinal inflammation (which can cause shortening of the bowel through smooth muscle contractions), pushes against the overall positive scaling we see between body mass and diversity across vertebrates [ 75 , 79 ]. Thus, we used height, which has been shown to be positively associated with bowel length [ 83–86 ], as an obesity/inflammation-independent proxy for measuring body size in humans. Overall, we were able to control for all of these potentially confounding variables in our regressions, and we found that the associations between height and gut alpha diversity were robust to the inclusion of these variables across two large, independent cohorts ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…El péptido GLP-1 promueve la proliferación de las células beta, la sensibilidad a la insulina, la cardioprotección, mejora la función cardiaca, favorece la neuroprotección y la neuroproliferación, y mejora la función cognitiva [21][22][23][24][25][26] .…”
Section: Incretinas Decretinas Y Diabetes Como Mala Adaptación Intest...unclassified
“…The average length is considered to be approximately 5 meters. 1 The variation in the intestinal length in humans is a topic of interest. Differences in measurement techniques, small study groups, and large interindividual variation have contributed to the uncertainty associated with defining a normal range of intestinal length.…”
Section: Introductionmentioning
confidence: 99%